Public Accountability through Soft Steering - Michiel S. de Vries; Iwona Sobis (Central European Public Administration Review)
This article argues that present-day procedures on public accountability miss the essence of being accountable. We suggest that alternatives are available in social psychology theory and network theory, which point to the decisive role of peers or experienced organization members. In this view, it is not leadership but middle management that is crucial in the socialization of newcomers in an organization to internalize values and to create a situation in which employers and employees develop mutual expectations about what is expected from one another and create multiplex networks in order to maintain such values.